Probing the application of the place-based policy concept – case studies of the chosen Integrated Territorial Investments in Europe - Klaudia Kamińska (Rozwój Regionalny i Polityka Regionalna)
The place-based approach is a new development paradigm that has been gaining popularity over the last decade or so. This is thanks to the European Union’s Cohesion Policy, which supports its implementation through tools such as Smart Specialisation, Community Led Local Development (CLLD) or Integrated Territorial Investments (ITI). The article’s main purpose is to probe to what extent the place-based concept was implemented within the Integrated Territorial Investment mechanism in the chosen European agglomerations during the programming period 2014–2020. Three agglomerations are presented: Olomouc Agglomeration in the Czech Republic, urban agglomeration Rijeka in Croatia, and Walbrzych Agglomeration in Poland using the case study method, the comparative analysis method and the questionnaire for responses from the representatives of the before mentioned agglomerations. The study shows that there are significant differences between countries in terms of how place-based policies are implemented. Agglomerations attempt to implement the idea presented by the European Union but do not fully exploit the potential of municipalities, applying the ITI guidelines without a clear understanding of the benefits of the approach. The conclusions of the presented study can make a valuable contribution to the literature on the subject and provide a starting point for further research and discussion on the necessary changes to the European Union’s Cohesion Policy.